Urgensi Penguatan Perlindungan Hukum Data Pribadi dalam Menghadapi Eksploitasi Ekonomi Digital - Vicky Daksa Tri Arya Hafilah; Muh Jufri Ahmad (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The rapid growth of the digital economy has transformed personal data into a strategic economic asset that underpins technology-based business activities. This transformation has intensified increasingly complex data processing practices, including service personalization, behavioral profiling, artificial intelligence-driven analytics, and data monetization, all of which may lead to the exploitation of personal data. Consequently, personal data protection can no longer be viewed solely as a matter of privacy but must also be understood as an issue of legal certainty, consumer protection, and the protection of fundamental rights within the digital economy. This study aims to analyze the forms and vulnerabilities of personal data exploitation in the digital economy and to examine the urgency of strengthening legal protection against such practices. This research employs a normative legal research method using statutory, conceptual, and comparative approaches. Legal materials were collected through library research and analyzed qualitatively using legal interpretation and argumentative analysis. The findings reveal that personal data exploitation is driven by the increasing economic value of data, unequal legal relationships between data subjects and data controllers, ineffective consent mechanisms, limited transparency, and challenges in supervision and law enforcement. These conditions indicate that the existing legal protection regime requires further strengthening to address the evolving characteristics of the digital economy. Strengthening legal protection should therefore emphasize preventive and adaptive legal mechanisms, a risk-based approach, meaningful consent, greater transparency in data processing, accountability in the use of digital technologies, effective regulatory oversight, and adaptive data governance centered on the protection of data subjects' rights. Accordingly, strengthening personal data protection constitutes a fundamental prerequisite for ensuring legal certainty, enhancing public trust, and fostering a fair and sustainable digital economy.